High Intensity low Aluminum Ion Energy Implantation into Titanium; Ion Implantation Technology (IIT 2018) - Ryabchikov A. I. Aleksandr Ilyich; Shevelev A. E. Aleksey Eduardovich; Sivin D. O. Denis Olegovich; Kashkarov E. B. Egor Borisovich; Bozhko I. A. Irina Aleksandrovna; Stepanov I. B. Igor Borisovich (2018, 2018)
Title screen